Force Generation in the Coiling Tendrils of Passiflora caerulea - Frederike Klimm; Thomas Speck; Marc Thielen (Advanced Science, 2023)
Abstract Tendrils of climbing plants coil along their length, thus forming a striking helical spring and generating tensional forces. It is found that, for tendrils of the passion flower Passiflora caerulea, the generated force lies in the range of 6–140 mN, which is sufficient to lash the plant tightly to its substrate. Further, it is revealed that the generated force strongly correlates with the water status of the plant. Based on a combination of in situ force measurements with anatomical investigations and dehydration‐rehydration experiments on both entire tendril segments and isolated lignified tissues, a two‐phasic mechanism for spring formation is proposed. First, during the free coiling phase, the center of the tendril begins to lignify unilaterally. At this stage, both the generated tension and the stability of the form of the spring still depend on turgor pressure. The unilateral contraction of a bilayer as being the possible driving force for the tendril coiling motion is discussed. Second, in a stabilization phase, the entire center of the coiled tendril lignifies, stiffening the spring and securing its function irrespective of its hydration status.